Nadużycia warunku losowości w definicji legalnej gry na automatach - Politowicz, Jerzy (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2020)
Gambling is one of human pastimes, often leading to loss of property or (and) addiction. The main feature of gambling is randomness. It is this feature, combined with the involvement of significant funds in the game, that makes gambling activity particularly vulnerable to various types of abuse. The most common area of abuse is a random definition of a legal slot game. Attempts by illegal operators to “circumvent” this definition are aimed at exempting the gambling games they organize from the limits of the applicable regulations. The latter is intended to capture as much of the gambling income as possible. The purpose of this article is present the definition of legal slot machine games, attempts to circumvent it in practice, and propose a solution to the latter problem. The literature on the subject proves that no one has undertaken a similar task so far, therefore the article may contribute to filling the gap in this area of law.
Keywords: gambling; slot machine games; legal definition; abuse